Challenges in data collection for enhancing productivity in Brazilian industrial processes - Haroldo Lhou Hasegawa; Rafael Sene de Lima; Vidal Dias da Mota Junior; Ricardo Luiz Perez Teixeira (Brazilian Journal of Operations & Production Management)
Goal: To understand the underlying reasons for low productivity in medium-sized metalworking companies and to evaluate the effectiveness of the productivity improvement techniques that have been implemented.